TATA KELOLA/TANGGUNG JAWAB SOSIAL PERUSAHAAN (CSR) DAN ETIKA DALAM MANAJEMEN STRATEGIS DALAM PENDIDIKAN - Sri Putrianingsih (The Center for Research and Community Service of Islamic Institute of Hasanuddin Pare-Kediri, 2023)
Abstract: The aplication of business ethics is a very important and needs special attention, since a good quality of school service can be obtained if the business ethic applications works effectively. The purpose of this study is to know the business ethics and theacher discipline of the quality of school service. the results of this study suggest that the implementation of business ethics falls at a high category. In addition, the effect of teacher work discipline on the quality of school service is civilised in moderate categories. based of research results, there are several recommendattions needed to improve quality management effectiveness, including continuous improvement and optimizing the total quality management approach. the reseach to discuss how corporate social responsibility must be reunderstood for better education. this suggests that there are mutually beneficial opportunities for national companies and governments to maintain human resources and overcome trade gaps and mismatches. Many companies often train and sponsor individuals to further study for their career advancement. It also indicates that some businesses angage in good behavior to attract prospective workers. In addition, the article argues that the providing of education, professional development and training will increase morale and employee job satisfaction, which in turn may lead to lower staff turnover and greater productivility levels in the workplace. Keyword: organizational development, corporate social responsibility, quality manajement services.